Recycling Lead Acid Car Batteries: Challenges and Prospects - Olishevska, V. E.; Ivanova, H. P.; Olishevskyi, H. S. (Science and Transport Progress, 2025)
Purpose. Road transport plays an important role in the functioning and development of the country's economy, but its operation is accompanied by a negative impact on the environment, consumption of scarce resources and an increase in the amount of waste, among which the most dangerous are spent lead-acid batteries. The main purpose of the study is to investigate the current state of recycling of lead-acid car batteries in the context of the economic crisis, energy shortages and intense environmental pollution, as well as to determine its prospects in Ukraine. Methodology. Today, there is a rapid increase in the level of motorization in our country, which causes a significant increase in the number of lead-acid batteries that need to be recycled. The lack of modern, efficient infrastructure for collecting used car batteries often leads to their ending up in landfills. This negative trend causes the loss of valuable secondary materials and environmental pollution. Current technologies for recycling lead-acid batteries are characterized by insufficient efficiency and require significant financial costs. An important challenge is the negative impact of battery recycling technology on the environment. Promising areas that will allow the recycling of lead-acid batteries include the creation of a modern infrastructure for battery collection and recycling and the development of recycling technologies, including the use of lead from batteries in the production of radiation-resistant concrete. A comprehensive study of the problem of recycling lead-acid batteries will satisfy the need to save resources and increase the rational use of resources contained in spent lead-acid batteries. Findings. The current state and problems of recycling lead-acid batteries for cars are analyzed. It is shown that battery scrap recycling allows solving two urgent problems: environmental protection and obtaining valuable secondary raw materials. The possibilities of using a vibrating jaw crusher with an inclined crushing chamber for the processing of battery scrap were investigated. Originality. A comprehensive analysis of the problem of recycling lead-acid car batteries was carried out, which allowed to identify specific features, development trends and challenges. The possibility of using a vibrating jaw crusher with an inclined crushing chamber for the processing of battery scrap is substantiated. Practical value. The main directions and problems of recycling lead-acid car batteries, the use of recycling products, including in the construction industry, are considered. It is proposed to use a vibrating jaw crusher with an inclined crushing chamber for the processing of lead-acid batteries.